Dare to “Decolonising the mind”:Meeting around the Thought of Ngugi wa Thiong'o - (:unkn) unknown (My University, 2011)
The aim of this article is to propose the basis for an open reflection on the sources of colonization through the literary approach proposed by Ngugi. In this context, it has been repetitively noted that the relations between Colonized and Colonizer (Memmi) are tenacious in our nature and everyday ways of thinking. And, contradictorily, the term "colonization" seems to evoke the days of yore, already accomplished, in our minds - one of the closed chapters in history - while the colonial-type armed conflicts and the process of recolonization have burst out again by the beginning of XXI century. Conquering the African resources, then to chase with all haste - using many stratagems - the least conciliatory leaders! The colonization is a process of the politico-economic exploitation that requires a mind control, of both the colonized and the colonizers.
Keywords: African Research